LAYANAN DAN KERUKUNAN AGAMA DI PERBATASAN NEGARA: STUDI KASUS DI DISTRIK SOTA MERAUKE - Muhamad Murtadho (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
This research aims to examine the needs of religious service and religious harmony in the borderlands of the country. This research uses a case study approach, studying the Sota District in Merauke. Sota District is located at the border between Indonesia and Papua New Guinea.This study finds that the level of religious service provided by the government is still insufficient and needs to be strengthened. Religious leaders lack resources and this is one of the main reasons for decreasing social and religious awareness, which can affect religious harmony. Further, interreligious harmony in this border region has not been well managed and there is the potential for social disorder in some cases.